The Analysis Study of Risk Factor, Management and Outcome of Asthma Bronchiale in Children : A Comprehensive Systematic Review - Hidayat, Nafian; Azwardi, Yusri; Saputra, Andri; Syafrianti, Veni; Rosa, Elvina (International Medical Journal Corp. Ltd, 2024)
Background: Asthma, the most common chronic respiratory disease (CRD) among children globally, affected an estimated 262 million people by 2019 and remains one of the most common CRDs across the life course. The aim: The aim of this study to show about risk factor, management and outcome of asthma bronchiale in children. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Asthma represents a dysfunctional interaction with our genes and the environment to which they are exposed, especially in fetal and early infant life. The increasing prevalence of asthma in all age groups indicate that our living environment and immunity are in imbalance with each other reacting.